Crossmodal Audiovisual Emotional Integration in Depression: An Event-Related Potential Study - Lu, Ting; Yang, Jingjing; Zhang, Xinyu; Guo, Zihan; Li, Shengnan; Yang, Weiping; Chen, Ying; Wu, Nannan (Frontiers in Psychiatry, 2021)
This article aims to investigate whether there is a difference in audiovisual emotional integration using a high-resolution event-related potential (ERP) technique. We designed a visual and/or auditory detection task. The behavioral results showed that the responses to bimodal audiovisual stimuli were faster than those to unimodal auditory or visual stimuli, indicating that crossmodal integration of emotional information occurred in both the depression and normal groups. The ERP results showed that the N2 amplitude induced by sadness was significantly higher than that induced by happiness. The participants in the depression group showed larger amplitudes of N1 and P2, and the average amplitude of LPP evoked in the frontocentral lobe in the depression group was significantly lower than that in the normal group. The results indicated that there are different audiovisual emotional processing mechanisms between depressed and nondepressed college students.